2021
DOI: 10.1029/2021ef002397
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Rainfall in Future Heavy Precipitation Events Related to Contracted Rain Area Despite Increased Rain Rate

Abstract: Heavy precipitation events (HPEs) can lead to deadly and costly natural disasters and are critical to the hydrological budget in regions where rainfall variability is high and water resources depend on individual storms. Thus, reliable projections of such events in the future are needed. To provide high‐resolution projections under the RCP8.5 scenario for HPEs at the end of the 21st century, and to understand the changes in sub‐hourly to daily rainfall patterns, weather research and forecasting (WRF) model sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 113 publications
(142 reference statements)
0
7
0
Order By: Relevance
“…Rain is defined by the rain rate, which is measured by (mm/h) according to the International Telecommunication Union (ITU) system [15]. The rain rates are specified as more than 50 mm/h for heavy rains and less than 0.25 mm/h for low rain rates [16]. Rain PL is also proportional to the rain's comparative size to the wavelength of the radio signal and the signal polarization due to the shape of the raindrop.…”
Section: 1 Propagation Losses (Pl) Due To Snow and Rainmentioning
confidence: 99%
“…Rain is defined by the rain rate, which is measured by (mm/h) according to the International Telecommunication Union (ITU) system [15]. The rain rates are specified as more than 50 mm/h for heavy rains and less than 0.25 mm/h for low rain rates [16]. Rain PL is also proportional to the rain's comparative size to the wavelength of the radio signal and the signal polarization due to the shape of the raindrop.…”
Section: 1 Propagation Losses (Pl) Due To Snow and Rainmentioning
confidence: 99%
“…Nevertheless, NWP models reproduce physical processes forced by real boundary conditions and are therefore expected to correctly reproduce the statistics of precipitation (e.g., Liu et al., 2017). Indeed, such models have been successfully employed for rainfall intensity and frequency (Ban et al., 2014; Ludwig & Hochman, 2021; Schär et al., 2016), including analyzing precipitation extremes in drylands (Armon et al., 2022; Dayan et al., 2021; Kunz et al., 2018; Liu et al., 2021; Rinat et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, previous studies have explored alternative methods for studying climate change impacts on convective events. There are commonly two approaches: event‐driven (Armon et al., 2022; Hibino et al., 2018; Kawase et al., 2020, 2021; Lackmann, 2013; Takayabu et al., 2015) and climatological (Kawase et al., 2019; Lenderink et al., 2021; Liu et al., 2017; Prein, Rasmussen, et al., 2017). The former focuses on the study of a specific event under different conditions related to climate change, while the latter focuses on the general changes of this type of event on a climatological time scale.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, such changes obscure the interpretation of the results. Several studies (Armon et al, 2022;Hibino et al, 2018;Kawase et al, 2020Kawase et al, , 2021Pall et al, 2017) have found that there is a decrease in convective and/or total rainfall amounts in simulations where a PGW approach was applied. It is unclear if this is associated with a change in vertical structure that may dampen the convective mechanisms associated with the original event as it was proposed by for example, Hibino et al (2018).…”
mentioning
confidence: 99%